A Suitability Analysis of Precast Components for Standardized Bridge Construction in the United Kingdom. (2016) - Kim, Min-Koo; McGovern, Scott; Belsky, Michael; Middleton, Campbell; Brilakis, Ioannis
Abstract: This paper presents the suitability of precast components for standardized UK bridges. The conventional design and construction of UK bridges is often criticized for being inefficient and unsafe as the majority of the work is carried out on-site, which requires lots of time and temporary works. The concept of Design for Manufacture and Assembly (DfMA) is employed in this study to overcome the limitations of the current bridge construction practice. First, underlying DfMA criteria for bridge construction are identified and a suitability analysis of precast components based on the identified DfMA criteria identified is conducted via an interview. Second, a case study on a bridge recently built for a highway bridge project is conducted to identify the feasibility of the potential precast components selected from the suitability analysis. The result of the case study demonstrates that the recommended precast components can be successfully used for future standardized bridges of the UK.